Investigation of polyurethane primer coating paint based on local palm oil with antimicrobial and anticorrotion agent formula bentonite-chitosan - Teuku Rihayat, .; Nurhanifa, .; Isra Adelya, Izzati; Sabila Yasara, Sa; Adi Saputra, Ismy; Sariadi, .; Muhammad Yunus, .; Irwan, .; Harunsyah, .; Alfian, Putra; Siregar, Januar Parlaungan; Cionita, Tezara (Chelo Global Business Incubator Foundation, 2024)
Paint is a product that is really needed to coat iron or steel materials such as industrial pipes, medical equipment, and so on. The sample formulation used was the addition of chitosan bentonite filler 2, 4, 6, 8% w/w. In TGA testing, the sample underwent single decomposition and showed the best results in the Polyurethane/Bentonite/Chitosan 8:8% w/w sample where the sample began to degrade at a temperature of 416.85 (℃). The bacterial test results showed the best results in the Polyurethane/Bentonite/Chitosan 8:8% w/w sample which had the widest inhibition zone with a value of 6.9 mm for E.Coli bacteria. The sample with the composition Polyurethane/Bentonite/Chitosan 8:8% w/w was the best sample where the sample experienced the smallest corrosion rate, namely 5.08 mpy. The application of this paint is to strengthen the durability of the building so that corrosion does not occur in the Hagu Barat Laut of Lhokseumawe because it is close to sea waters which have air levels that are quite susceptible to corrosion.